2022
DOI: 10.3389/fphar.2022.822726
|View full text |Cite
|
Sign up to set email alerts
|

Oleandrin: A Systematic Review of its Natural Sources, Structural Properties, Detection Methods, Pharmacokinetics and Toxicology

Abstract: Oleandrin is a highly lipid-soluble cardiac glycoside isolated from the plant Nerium oleander (Apocynaceae) and is used as a traditional herbal medicine due to its excellent pharmacological properties. It is widely applied for various disease treatments, such as congestive heart failure. Recently, oleandrin has attracted widespread attention due to its extensive anti-cancer and novel anti-viral effects. However, oleandrin has a narrow therapeutic window and exhibits various toxicities, especially typical cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 124 publications
0
10
0
Order By: Relevance
“…Further validation on animal models may strengthen the evidence for oleandrin as a promising new senolytic. A caveat, however, is that cardiac glycosides that have been employed in heart conditions have severe limitations due to toxicity 76 , and our results suggest that oleandrin is not an exception because of its narrow therapeutic range and cardiotoxicity, and hence its use as systemic senolytic should be considered cautiously. The high potency of oleandrin could potentially benefit senolytic therapies administered locally on the site of damage; clinical trials are currently assessing such local administration of senolytics for osteoarthritis 10 , 77 .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Further validation on animal models may strengthen the evidence for oleandrin as a promising new senolytic. A caveat, however, is that cardiac glycosides that have been employed in heart conditions have severe limitations due to toxicity 76 , and our results suggest that oleandrin is not an exception because of its narrow therapeutic range and cardiotoxicity, and hence its use as systemic senolytic should be considered cautiously. The high potency of oleandrin could potentially benefit senolytic therapies administered locally on the site of damage; clinical trials are currently assessing such local administration of senolytics for osteoarthritis 10 , 77 .…”
Section: Discussionmentioning
confidence: 84%
“…From a translational point of view, we highlight that the three senolytics identified in this study are natural products found in traditional herbal medicines: Ginkgo biloba (ginkgetin) 79 Nerium oleander (oleandrin) 76 and Periploca sepium (periplocin) 80 . Oleandrin and periplocin belong to the group of cardenolide glycosides, which are highly potent cardioactive agents, while ginkgetin is a biflavone with a broad pharmacological spectrum.…”
Section: Discussionmentioning
confidence: 88%
“…Campestanol ( 83 ), SM(d18:0/0:0) ( 84 ), ethoxyquin ( 85 , 86 ), phendimetrazine ( 87 ), 10-deoxymethymycin ( 88 ), anandamide (20:2, n -6) ( 89 ), and miltefosine ( 90 ) have hypocholesterolemic, cell signaling, antioxidant, anticarcinogenic, anorexigenic, antibacterial, fatty acid neurotransmitter, and antileishmanial effects, while no bioactivity has been reported for 11-amino-undecanoic acid, d -pantetheine 4′-phosphate, and 3-hydroxytetradecanedioic acid. The biologically active compounds diethylcarbamazine, acetylsalicylic acid (aspirin), 2-propyl-9 Z -octadecenoic acid, and oleandrin ( 72 , 91 95 ) detected in the bioactive fraction of PBR11Fr-2 exhibited anti-inflammatory effects, nonsteroidal anti-inflammatory action, antiplasmodial activity, anticancer effects, novel antiviral activity, and anorexigenic effects. However, there is no bioactivity reported for 12,14-pentacosadiynoic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have verified that oleander can be quickly absorbed in the gastrointestinal tract and results in immediately toxic effects after oral administration [3]. The stomach contents from patients or the dead could be suitable for determining oleander poisoning [22].…”
Section: Detection Of Oleander-containing Materials With Qpcrmentioning
confidence: 99%
“…Nerium oleander, also known as oleander, is a highly toxic shrub with beautiful flowers. The presence of various cardiac glycosides in all the parts of the oleander plant are the main toxins that cause acute cardiotoxicity [2,3]. Trace consumption of oleander is enough to trigger dizziness, emesis, diarrhea, arrhythmia, and even death.…”
Section: Introductionmentioning
confidence: 99%